DISCOURSE ANALYSIS OF THE WEBSITE CONTENT OF P2B (PUSAT PENGEMBANGAN BISNIS) UIN SYARIF HIDAYATULLAH JAKARTA - Rosyida, Ulva Fatiya; Subchi, Imam; Saefudin, Arif; Wahyudhi, Johan; Conita, Syifa; Rahmawati, Wulan (Institut Agama Islam Ngawi, 2025)
This study aims at analyzing and describing the discourse of the official website content of Pusat Pengembangan Bisnis (P2B) UIN Jakarta using Discourse Analysis. The objectives involve identifying communicative deficiencies and proposing strategies for improvement. The descriptive qualitative method involves textual and multimodal coding of website content. Results indicate that the content lacks multimodal features (e.g. visuals, icons), absence of feedback forms, and multilingual content. Recommendations include adopting conversational register, integrating visual resources, providing multilingual options, and incorporating interactive feedback features. These strategies are crucial as UIN Jakarta transitions toward Public Legal Entity (PTN-BH) status, where communicative digital discourse aligns with institutional transparency and competitiveness. Keywords: Discourse Analysis, P2B Website, UIN Jakarta